2020
DOI: 10.3390/ma13214828
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Oxychloride Cement Composites Lightened with Granulated Scrap Tires and Expanded Glass

Abstract: In this paper, light burned magnesia dispersed in the magnesium chloride solution was used for the manufacturing of magnesium oxychloride cement-based composites which were lightened by granulated scrap tires and expanded glass. In a reference composite, silica sand was used only as filler. In the lightened materials, granulated shredded tires were used as 100%, 90%, 80%, and 70% silica sand volumetric replacement. The rest was compensated by the addition of expanded glass granules. The filling materials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Based on the obtained results it is possible to claim that the Liaver incorporation outweighs the effect of borax addition in terms of total open porosity—even with a huge spread value, and the high total open porosity is achieved. This observation is supported by the previous research conducted by Pavlíková et al [ 53 ], where the growing share of Liaver in MOC-based mortars caused the increase in open porosity.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the obtained results it is possible to claim that the Liaver incorporation outweighs the effect of borax addition in terms of total open porosity—even with a huge spread value, and the high total open porosity is achieved. This observation is supported by the previous research conducted by Pavlíková et al [ 53 ], where the growing share of Liaver in MOC-based mortars caused the increase in open porosity.…”
Section: Resultssupporting
confidence: 86%
“…Both applied aggregates were chosen as they are not only lightweight, but also sustainable (“green”) as waste glass and was crumb rubber are turned back into production process and thus transformed to profitable materials. The use of both crumb rubber and expanded glass is supported by the previous research focused on the use of lightweight aggregates in a different group of magnesia-based cements, specifically magnesium oxychloride cement [ 53 ]. The topic of lightweight aggregates was pursued, as for MKPC-based composites this problematic has not yet been properly researched and above all the combination of MKPC and higher volume of various lightweight aggregates still needs to be thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium oxychloride cement, known as magnesium cement for short, was invented by the Swedish scholar Sorel in 1867 and was mainly composed of the MgO-MgCl 2 -H 2 O ternary system [7][8][9][10][11][12]. The magnesium oxychloride cement has lots of the advantages, for instance, early strength, good fire resistance, excellent abrasion resistance and low thermal conductivity [13][14][15][16], which is widely used in arts and crafts, composite boards and building materials and other fields [17][18][19][20], and is especially applied to the partition wall board having light weight, high strength, stable in performance, easy to transport, cut and installation, etc. When the new crown epidemic was raging around China, most simple temporary hospitals or isolated areas, such as Leishenshan Hospital and Huoshenshan Hospital (in Wuhan), were built with the partition wall board.…”
Section: Forewordmentioning
confidence: 99%
“…Among these compounds, 5Mg(OH) 2 •MgCl 2 •8H 2 O mostly consists of needle-shaped microstructures, whereas the morphology of Mg(OH) 2 gel is mostly scaly and fibrous [7,8]. Studies have shown that the 5•1•8 phase is the main strength phase of magnesium oxychloride cement, and this phase provides the mechanical properties for magnesium oxychloride cement [9].…”
Section: Introductionmentioning
confidence: 99%